Zagadnienie rewizji Karty Narodów Zjednoczonych - Henczel, Achilles (Wydział Prawa i Administracji UAM, 1984)
The present article concerns a question of revising the UN Charter, which is essential both from the political and international law point of view. It is regulations of the Charter which are the legal guarantee of maintaining world peace and security. Changes in international community which took place in the decades of fourties and fifties in the scope of political differenciation of states, esp. the so-called great powers and in completion of the de-colonization resulted in increasing tendencies to revise several provisions of that document. Main subject of activities were: abolishing or limiting a principle of permanent membership of the Security Council, and the related right to veto, another definition of a role and competence division of particular main organs of the organization- e.g. activities of the General Assembly and Security Council in the scope of maintaining and securing peace, defining a new formula of the Trusteeship Council In the opening part of the article the author presents general procedures of introducing amendments and changes in agreements referring to preparatory works to the Vienna Conference on the Law of Treaties and to the relevant regulations providec by the Convention of 1969. Next, the author examines a question of revising the Charter in the light of its own provisions proving a lack of substantial differences between the procedure of art. 108 on introducing amendments and the procedure provided in art. 109, esp. in its par. 2 on calling the Conference for the Purpose of Revising. The main part of the study presents the origins and works on the revision of the Charter, on the grounds of the activities undertaken in the General Assembly and in the Sixth Committee and in other ad hoc appointed bodies. The author concludes his remarks focusing on the perspectives of realization a process of revising the UN Charter which seems to be heavily affected by the political designs of states of groups of states-members of the UN.
The question of revising the United Nations Charter